Design of Soil Moisture Telemetry System Using cluster-based Wireless Sensor Networks - Annisa Widuri Murti Utami; Dany Primanita Kartikasari; Adhitya Bhawiyuga; Reza Andria Siregar; Fariz Andri Bakhtiar (Faculty of Computer Science (FILKOM) Brawijaya University, 2022)
Agriculture is an art and science used to cultivate the land, grow crops, and raise livestock. Agricultural land in Indonesia has different soil quality in each region. Soil quality for agriculture can have an impact on crops. Therefore, a Wireless Sensor Network (WSN) was created to make it easier to determine soil moisture. This system can help to monitor the condition of soil moisture content. WSN applies a Cluster-Based Algorithm, and the protocol used in WSN is a Low Energy Adaptive Clustering Hierarchy (LEACH). WSN will search for the cluster head, and then the sensor node will send the results of soil moisture sensing data to the cluster head for further data aggregation. Then, the results of the aggregation data will be sent to the sink node and then forwarded to the cloud. Data aggregation can make the sink stay longer than 30 minutes than the sink node that receives data without aggregation. Sink nodes that do not receive aggregation data also use more load current than sinks that receive aggregation data. The test results of the average response time to find new cluster heads have an average time of 6023.4 milliseconds. The maximum distance between nodes to transmit data to each other is 100 meters.